Latina/o Midwest Reader - Fox, Claire F.; Vaquera-Vásquez, Santiago R., 1966-; Valerio-Jimenez, Omar S. (Omar Santiago), 1963- (Book collections on Project MUSE., 2017)
"From 2000 to 2010, the U.S. Latino population increased by 44 percent. It grew even more--by more than 73 percent--in eight out of twelve midwestern states over the same years. This interdisciplinary anthology of essays examines the history, education, literature, art, and politics of Latinos in the Midwest in view of the demographic changes experienced by states in this region with growing Latino populations and the recent immigration raids in the Midwest. Through brief readings on topics ranging from immigration to labor history and expressive culture, the anthology sheds light on the region's history, as well as its cultural dynamics, population shifts, and social movements based in labor, religion, and civil rights."--Provided by publisher.